A Note on Growth Projections for Capital-Constrained Economies Working Paper Series Paper No.2/2001-PC - (:unkn) unknown (Planning Commission, 2001)
This working paper by Pronab Sen examines the limitations of the Harrod-Domar model in projecting economic growth for capital-constrained economies, highlighting its oversimplified assumptions, including steady-state growth, instantaneous investment translation, and continuous time. The study proposes corrective measures such as discrete time adjustments, accounting for gestation lags, and incorporating capital depreciation. An integrated model combining these adjustments provides a more accurate estimation of the investment required to achieve target growth rates. The paper emphasizes that refined modeling is essential for effective economic planning and investment strategy in developing nations.
Perspective Planning Division Planning Commission Government of India, May, 2001
Perspective Planning Division Planning Commission Government of India, May, 2001
Keywords: Harrod-Domar Model; Capital-Constrained Economies; Economic Growth; Incremental Capital-Output Ratio; Discrete Time Adjustment; Gestation Lags; Capital Depreciation; Investment Requirements; Integrated Growth Model; Developing Countries